Systematic literature review on the short pasta noodles reinforced with seaweed - Janampa Salvatierra, Angelo Jean Pierr (2023)
In the present research, through a systematic literature review, we seek to describe the application of seaweed in the production of noodles, as an alternative to traditional preparation and to improve the nutritional content of noodles. For this, in the first place, papers were extracted from different databases such as Scopus and Google Scholar. Then, the most relevant information was analyzed and extracted from each scientific article. With this information, the objectives were answered. Finally, the results were analyzed in detail and the doors were opened for new research on noodles reinforced with seaweed, but centralized in Peru. Thanks to this research, it can be said that the application of seaweed in small proportions (<= 5%) is beneficial at the nutritional level, since it increases the amount of proteins, fiber and minerals, as well as decreases the amount of carbohydrates and fats.